Peningkatan Hasil Belajar PKn melalui Pembelajaran Value Clarification Technique (VCT) pada murid kelas IV A SD Negeri Samata Kabupaten Gowa - Muhajir Muhajir (Universitas of Muhammadiyah Makassar, 2017)
Problems in this research is the low learning outcomes of Civics to fourth graders A State Elementary School Samata Gowa District. This type of research is a classroom action research (Classroom Action Research) consisting of two cycles where each cycle is held 4 times a meeting. The research procedure includes planning, action implementation, observation and reflection. Subjects in this study were students of class IV A State Element Samata Gowa District as many as 38 people. The results showed that in the first fully completed cycle of 38 students only 23 students or 61% who fulfilled the Minimum Exhaustiveness Criteria (KKM). In the second cycle of 38 students there are 34 students or 89% have met the KKM and have been classically fulfilled the average value obtained by 78.94 or are in high category. The results showed that the average of student learning outcomes in cycle I is 70.52 and in cycle II increased to 78.94.Keywords: Learning Outcomes, Value Clarification Technique (VCT)